Relationship Between Leaf Photosynthesis and Nitrogen Content of Field-Grown Rice in Tropics - Peng, Shaobing; Cassman, Kenneth G.; Kropff, Martin J. (Wiley, 1995)
A field‐derived relationship between maximum single leaf net photosynthetic rate under saturating light (Amax) and leaf N content per unit leaf area (Na) is not available for rice (Oryza sativa L.). The rice simulation model ORYZA1 estimates aboveground dry matter production based on the relationship between Amax and Na determined previously under greenhouse‐growth chamber conditions. The objectives of this study were to establish to relationship between Amax and Na under field conditions and to determine whether the field‐derived relationship could improve ORYZA1 estimation of aboveground dry matter production of tropical irrigated rice. Rice plants were grown in the field with different N rates in the 1993 dry season. The Amax and Na were determined at 38 and 88 d after transplanting. Aboveground dry matter was determined at physiological maturity. Dry matter production data at physiological maturity from four other field experiments were used for model evaluation. There was a close correlation between Amax and Na under field conditions (r2 = 0.88). Compared with the relationship between Amax and Na as determined under greenhouse‐growth chamber conditions in previous studies, higher Amax was observed at low Na in this field study. When the field‐derived relationship between Amax and Na was used, ORYZA1 estimation of dry matter production was improved for rice grown in tropical irrigated environments.